Inequality, welfare and poverty theory and measurement - Amiel, Yoram; Bishop, John A. (JAI, 2003)
Research on Economic Inequality, Volume 9, Inequality, Welfare and Poverty: Theory and Measurement continues the series of original, timely and useful papers in applied welfare analysis. This volume contains fifteen papers on inequality theory, economic mobility, issues in empirical estimation, and empirical studies. The theory papers address the link between inequality and social welfare. The mobility papers address issues of unequal growth and intergenerational mobility. The estimation papers address data weighting and equivalent scale issues. The final section presents empirical papers on poverty and inequality for a variety of countries.
Keywords: Equality.; Poverty.; Welfare economics.; Business & Economics -- Management.; Poverty & unemployment.; Social theory.; elektronické knihy; electronic books